Simulating a Temperature, Stress And Strain FBG Sensor for Troposphere Layer - Wasmaa A. Jabbar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this study, a simulation and design for a temperature (T) sensor are investigated by using the fiber Bragg gratings (FBG). The study investigated and characterized the FBG regarding maximum reflectivity, bandwidth, and the influence of applied strain on the shift in Bragg wavelength (λB). This is via measuring sensitivity of wavelength shift under strain in an optical sensing system. The response of FBG sensors was also investigated and optimized. Uniform FBG spectra and theoretical comparisons were conducted considering the influence of several selected external strain/stress (S) values: 101.325, 89.874, 79.495, 70.108, 61.640, 54.019, 47.181, 41.060, 35.599, 30.742, 26.436. The Optisystem 16 software is analyzing these two types of effects. The measured parameters, such as sensitivity, were determined by using a white light source. The light source operating wavelength was 1550 nm. This is to design the sensor especially for troposphere that have high sensitivity (1279.7472 pm/oC. The sensitivity obtained exhibited varying values between 1279.7472 and 1239.7551 for strain. The peak sensitivity observed is associated with 550 nm of wavelength. Result for measured sensitivity against S by the FBG sensor was 15.5087 pm/oC with sensor length 20 mm. While it was found equals 15.5131 pm/oC with sensor length 10 mm. T sensing is simulated for selected values (15, 8.5, 2, -4.5, -11, -17.5, -24, -30.5, -37, -43.5, -50 oC). Resulted sensitivity was found to fluctuate fitting sine, Long Normal, and Boltzmann functions, indicating large sensitivity for the simulated sensor responses.